Pengaruh Biaya Operasional Terhadap Pendapatan Operasional (BOPO) Dan Net Interest Margin (NIM) Terhadap Return On Asset (ROA) - Diah Ayu Dwi Nurmavita; Ayyu Astri Wiguna; Muhammad Saddam Ihza Husain; Alfiana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study is proxied by Return on Assets (ROA), while operational efficiency is measured using Operating Costs to Operating Income (BOPO) and net interest income is measured by Net Interest Margin (NIM). A quantitative approach with panel data regression analysis is used in this study, where the best model selected is the Fixed Effect Model based on the results of the Chow Test and the Hausman Test. The data used are secondary data from the annual financial statements of Bank Mandiri, BRI, BNI, and BTN with a total of 32 observations. The results of the analysis show that BOPO has a negative and significant effect on ROA, which means that an increase in BOPO will reduce bank profitability because high operating expenses erode profits. Conversely, NIM has a positive and significant effect on ROA, so that the higher the net interest margin obtained by the bank, the higher the resulting profitability. Simultaneously, BOPO and NIM have a significant effect on ROA with an adjusted R² value of 0.971972, indicating that both variables are able to explain 97.19% of the variation in ROA changes. This study confirms that increasing the profitability of state-owned banks is largely determined by the level of operational efficiency and the effectiveness of intermediation strategies in generating interest income.